Leadership Style and Role of a Female Principal in Improving the Quality of Education at Bondalem Elementary School - Vika Mutiara Ghozelin; Fakhrur Syaifudin (al-fikrah: Jurnal Manajemen Pendidikan, 2022)
One of the factors of success in education is closely related to the style and role of the principal in leading the school. Currently, there are many assumptions about how leadership is equivalent to masculinity and considers that women are less competent in leading. This research aimed to find out how the leadership style and role of female principals in improving the quality of education. This research was qualitative research in which the data were collected at Bondalem Elementary School of Bantul using interview and documentation methods. Based on this research, the leadership style used by the principal of Bondalem Elementary School of Bantul is authoritarian, democratic, and charismatic. The implementation of her leadership role can encourage all aspects of the school and contribute to developing and improving the quality of education